2021
DOI: 10.47432/2020.36.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Plant Growth Regulators and Dates Planting on Spring Maize Production Under Agro-Climatic Conditions of Faisalabad, Pakistan

Abstract: Maize is a widely grown cereal crop worldwide, butthe heat stress and delayed sowing of maize are major constraints that result in declining the maize productivity.Therefore, the current study was designed to investigate the growth promoting effect of different growth regulators i.e., salicylic acid, methyl jasmonate, and humic acid at multiple sowing times in  spring maize. Experiment was laid out in randomized complete block design having split-plot arrangement with three replications having plot size of 6m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Exogenous growth hormones were also used to control seed germination, root elongation, cell development, and tiller formation in C 4 plants cultivated under trace-metal contaminated soils ( Maghsoudi et al, 2019 ). Similarly, in cereals like maize foliar application of plant growth hormones under abiotic stresses considerably improved the leaf area, plant growth, dry biomass, and stem diameter of C 4 plants ( Tran and Popova, 2013 ; Qandeel et al, 2020 ). It was reported that exogenous application of various types of brassinosteroids, i.e., 28-homobrassinolide, and 24-epibrassinolide significantly enhanced the biomass and productivity of maize, sugarcane, and sorghum grown under abiotic stresses, i.e., drought, salinity, and trace-metal contaminated soils ( Tanveer et al, 2018 , 2019 ).…”
Section: Tools and Strategies To Enhance Biomassmentioning
confidence: 99%
“…Exogenous growth hormones were also used to control seed germination, root elongation, cell development, and tiller formation in C 4 plants cultivated under trace-metal contaminated soils ( Maghsoudi et al, 2019 ). Similarly, in cereals like maize foliar application of plant growth hormones under abiotic stresses considerably improved the leaf area, plant growth, dry biomass, and stem diameter of C 4 plants ( Tran and Popova, 2013 ; Qandeel et al, 2020 ). It was reported that exogenous application of various types of brassinosteroids, i.e., 28-homobrassinolide, and 24-epibrassinolide significantly enhanced the biomass and productivity of maize, sugarcane, and sorghum grown under abiotic stresses, i.e., drought, salinity, and trace-metal contaminated soils ( Tanveer et al, 2018 , 2019 ).…”
Section: Tools and Strategies To Enhance Biomassmentioning
confidence: 99%